Bioconjugated Carbon Dots for Delivery of siTnfα to Enhance Chondrogenesis of Mesenchymal Stem Cells by Suppression of Inflammation. (28th March 2019) - Liu, Jianwei; Jiang, Tongmeng; Li, Chun; Wu, Yang; He, Maolin; Zhao, Jinmin; Zheng, Li; Zhang, Xingdong
Abstract : Although a promising strategy, the mesenchymal stem cell (MSC)-based therapy of cartilage defects is sometimes accompanied with chronic inflammation during the remodeling status, which may hinder cartilage regeneration. During this process, the inflammatory cytokine tumor necrosis factor α (TNFα) plays an important role and may be a potential target. In this study, we investigated the effect of Tnfα RNA interference by introducing a functional and highly safe carbon dot (CD)-SMCC nanovector synthesized by bioconjugation of CDs with a protein crosslinker, sulfosuccinimidyl-4-(N-maleimidomethyl) cyclohexane-1-carboxylate (sulfo-SMCC), as the vehicle of the silenced TNFα (si Tnfα ) on chondrogenesis of MSCs. The results showed that CD-SMCC displayed intense fluorescence with well-dispersed and positively charged properties, which favored effective binding and delivering of si Tnfα into the MSCs. CD-SMCC-si Tnfα nanoformula also exhibited considerably high transfection efficiency and nearly no cytotoxicity, which is preferred over commercial polyethyleneimine. Interference of Tnfα by CD-SMCC-si Tnfα markedly promoted the chondrogenesis of MSCs, as indicated by upregulating cartilage-specific markers. Furthermore, in vivo exploration indicated that CD-SMCC-si Tnfα transfected MSCs accelerated cartilage regeneration. In conclusion, this study demonstrated that in combination with the novel CD-SMCC nanovector, targeting Tnfα may facilitate stem cell-based therapy of cartilage defects. Stem Cells Translational Medicine   2019;8:724&736 : Abstract : Carbon dot-succinimidyl-4-(N-maleimidomethyl) cyclohexane-1-carboxylate had favorable biocompatibility, low toxicity, high transfection efficiency, and excellent complexing ability with small interfering RNA, which is preferred over the commercial transfection reagent, PEI25k. In addition, it was detected that silencing of tumor necrosis factor-α in mesenchymal stem cells markedly promoted the chondrogenic differentiation of mesenchymal stem cells and further accelerated cartilage regeneration in vivo.